Detox handbook - Harper, Jennifer, frey50 (New York : DK Natural Health Magazine, 2002)
A one stop resource on how to have a healthy body, glowing skin, a clear mind, and a streamlined life. Provides safe, no-nonsense information an ddebunks the many detoxing myths.
Keywords: Detoxification (Health); Fasting; Rejuvenation